Feedback Regulation of sPLA2-COX/5-LOX-Ca2+ in Seminal Plasma and Its Impact on Sperm Quality Parameters - Liu Y; Dai L; Zhang F; Liu Y; Li X; Ma W (Journal of Inflammation Research)
Yongjie Liu, Liang Dai, Fan Zhang, Yang Liu, Xu Li, Wenzhi Ma Reproductive Medical Center, Yinchuan Maternity and Child Health Care Hospital, Key Laboratory of Fertility Preservation and Maintenance of Ministry of Education, School of Basic Medical Sciences, Ningxia Medical University, Yinchuan, People’s Republic of ChinaCorrespondence: Wenzhi Ma, Reproductive Medical Center, Yinchuan Maternity and Child Health Care Hospital, Key Laboratory of Fertility Preservation and Maintenance of Ministry of Education, School of Basic Medical Sciences, Ningxia Medical University, No. 56 Wenhua West Street, Yinchuan, Ningxia, People’s Republic of China, Email mawenzhi126@126.com Yongjie Liu, Reproductive Medical Center, Yinchuan Maternity and Child Health Care Hospital, Key Laboratory of Fertility Preservation and Maintenance of Ministry of Education, School of Basic Medical Sciences, Ningxia Medical University, No. 56 Wenhua West Street, Yinchuan, Ningxia, People’s Republic of China, Email lyj1722006@126.comBackground: Male reproductive health is of growing concern. Sperm quality declines due to multiple factors. The role of AA metabolic network in sperm quality is unclear, and AA/COX’s protection under heat stress needs study.Aim: This study aimed to investigate the relationship between seminal plasma arachidonic acid (AA) metabolic network markers and sperm quality, as well as explore the protective effects of AA and cyclooxygenase (COX) on sperm under heat stress.Methods: We analyzed 164 seminal plasma samples from 164 male infertility patients, categorized by sperm concentration and motility (PR < 32% vs PR ≥ 32%). A heat-stressed weak spermatogenesis model (37– 42°C) was established, and AA/COX were added in vitro to assess their impact on sperm quality.Results: Significant correlations were found between AA pathway markers (PL, sPLA2, AA, COX1/2, PGE1, PGF2α, 5-LOX, LTB4) and sperm parameters (motility, acrosome reaction, mitochondrial function, DNA fragmentation). A predictive model combining PL, AA, and COX1 effectively assessed sperm quality. In vitro, 100 pg AA ± 300 pg COX1 protected sperm at 42°C by upregulating COX2, PGE1, and PGF2α while reducing LOX/LTB4 and modulating Ca²+ levels, improving acrosome reactivity and reducing oxidative stress.Conclusion: Seminal plasma AA metabolism strongly influences sperm quality, likely via sPLA2-COX/5-LOX-Ca²+ feedback mechanisms. The PL-AA-COX1 model may serve as a sperm quality predictor, and AA/COX1 supplementation could protect sperm under heat stress.Keywords: seminal plasma, sPLA2-COX/5-LOX-Ca2+, positive and negative feedback, spermatozoa, quality